P-Limitation Promotes Carbon Accumulation and Sinking of Emiliania huxleyi Through Transcriptomic Reprogramming - Wang, Cong; Wang, Jingtian; Li, Ling; Wang, Yujie; Lin, Senjie (Frontiers in Marine Science, 2022)
Global warming is expected to cause decreases in nutrient availability, photosynthesis, and potentially carbon export in the ocean. But how, and by what molecular mechanisms, nutrient limitation affects biological pump (BP) efficiency of phytoplankton are poorly understood. Here, using transcriptomics, miRNAomics, and physiological measurements, we report that phosphorus (P)-limitation increased cell carbon and calcium contents and sinking rate of the cosmopolitan phytoplankton Emiliania huxleyi. Under P-limitation, when photosynthesis was depressed, there were substantial increases in cellular organic (3.4-fold) and inorganic (5-fold) carbon contents due to cell division arrest and, as our transcriptomic data suggest, CO2 incorporation into C4 compounds. Furthermore, calcification was increased by 46% through transcriptional and epigenetic regulations. An increase in sinking rate by 37-44% was detected. Although calcification releases equivalent amounts of CO2, the considerable increase in cellular carbon content and sinking rate far outweighed the CO2 release, leading to an elevated efficiency of carbon export by E. huxleyi¬, which would partially offset the decrease in BP capacity resulting from lower growth rate under P deficiency. However, how the observed sinking rate and its increase under P limitation on the laboratory cultures will translate into BP efficiency still requires further examination using in situ or mesocosm experiments.